The needs and experiences of women with gestational diabetes mellitus from minority ethnic backgrounds in high-income nations: A systematic integrative review. Issue 2 (March 2023) - Tzotzis, Louise; Hooper, Mary-Ellen; Douglas, Angela; Kurz, Ella; Atchan, Marjorie; Spiller, Sarah; Davis, Deborah
Abstract: Background: Gestational diabetes mellitus (GDM) represents a growing challenge worldwide, with significant risks to both the mother and baby that extend beyond the duration of the pregnancy and immediate post-partum period. Women from ethnic minority groups who access GDM care in high-income settings face particular challenges. The aim of this systematic integrative review is to explore the experiences and needs of women with GDM from select ethnic groups in high-income healthcare settings. Methods: For the purposes of this systematic integrative review, a comprehensive search strategy explored the electronic databases CINAHL, Medline, Web of Science, and Scopus were searched for primary studies that explored the needs and experiences of women with gestational diabetes from select ethnic minority groups living in high-income nations. The ethnicity of the women in the study included: East, South and Southeast Asian, Indian subcontinent, Aboriginal/First Nations, Torres Strait Islander, Pacific Islander, Māori, Middle Eastern, African, or South/Latina American. Studies were assessed with the Crowe Critical Appraisal Tool and findings were synthesised with thematic analysis. Results: This review included 15 qualitative studies, one mixed method, and one cross-sectional study. Six high-income nations were represented. The voices and experiences of 843 women who originated from at least one ethnic minority group are represented. Four major themes were constructed: psychological impact of GDM, GDM care and education, GDM and sociocultural impact, and GDM and lifestyle changes. Discussion and conclusion: Limitations exist in the provision of culturally appropriate care to support the management of GDM in women from select ethnic groups in high-income healthcare settings. Women require care that is culturally appropriate, considering the individual needs and cultural practices of the woman. Engaging a woman's partner and family ensures good support is provided. Culturally appropriate care needs to be co-designed with communities so that women are at the centre of their care, avoiding a one-size-fits-all approach.